KUALITAS PENYELENGGARAAN PENDIDIKAN AGAMA PADA PROGRAM PAKET A, B, DAN C - Farida Hanun (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This research is to identify: the progress of the religious educations’ program towards the package A, B, and C program that are spread to 7 provinces in Indonesia. Survey method appears as the method used in this research. The result of the research indicates: 1) the obligation for the people to attend the educational religious course is considered still not well implemented by the institutions’ packages, 2) the amount of religious tutors in the establishment of religious education by the third package is still few, 3) religious tutors with irrelevant background to the formal education still exist 4) There are program organizers that are still considering the implementation of religious education appear not as a compulsory lesson, 5) the coordination between the ministry of religious affairs and the ministry of education and culture is still considered low related to the religious education’s establishment on the package.